Adopting Sulh-e-Kull for Political Religious Moderation in Indonesia: Lessons from the Mughal Dynasty - Alauddin, Badat (Indonesian Scientific Publication, 2024)
This study examines the relevance of religious moderation in Indonesia by analyzing Sulh-e-Kull and Din-e-Ilahi, policies of Sultan Akbar during the Mughal Dynasty. Using a qualitative-descriptive approach, it explores how Akbar’s tolerance policies—such as abolishing the jizyah tax, establishing interfaith spaces, and promoting interfaith marriages—fostered social and political integration. The findings highlight that religious moderation not only preserves societal harmony but also strengthens political legitimacy. However, challenges arise from misconceptions equating moderation with absolute pluralism. Learning from Akbar’s successes and criticisms, Indonesia can adopt tolerance-based governance while upholding religious principles. This study concludes that effective religious moderation requires respecting diverse beliefs without compromising core faith values. Policymakers should implement inclusive policies, encourage interfaith dialogue, and promote historical awareness to sustain national unity in a pluralistic society.